1984
DOI: 10.1046/j.1468-2982.1984.0402135.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Paroxysmal Hemicrania: Heart Rate Changes and ECG Rhythm Disturbances. A Computerized Analysis of 24 h Ambulatory ECG Recordings

Abstract: Ambulatory ECG recordings have been carried out in five patients suffering from CPH. During the study a total of 105 attacks occurred. Contrary to findings in cluster headache, no typical pattern of heart rate change was found in association with attacks of CPH. A striking finding in all patients, however, was that there were often large and rapid variations in heart rate which could be observed "before", "during" or "after" the attacks. One patient developed bradycardia and sino-atrial block and another bundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Bradycardia could be formidable, decreasing to 20 beats per minute [32]. In our case, less drastic irregularity was present (and in a later series) [33]. These phenomena could possibly fit with a cholinergic stimulation, less marked in CPH than in cluster headache.…”
Section: Cardiac Dysrhythmiasupporting
confidence: 43%
“…Bradycardia could be formidable, decreasing to 20 beats per minute [32]. In our case, less drastic irregularity was present (and in a later series) [33]. These phenomena could possibly fit with a cholinergic stimulation, less marked in CPH than in cluster headache.…”
Section: Cardiac Dysrhythmiasupporting
confidence: 43%
“…Almost all migraine patients have nausea or vomiting; many of them also have other gastrointestinal symptoms, e.g. [7][8][9][10][11][12][13][14][15][16][17][18] As a result of plasma catecholamine determinations, it has been suggested that patients with migraine show sympathetic hypofunction, the defective noradrenergic activity being an important pathogenic factor, 15 but quite opposite results have also been reported. Extraordinary sweating can be encountered during migraine attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic studies have yielded inconsistent results, although increased lacrimation and nasal secretion on the symptomatic side and decreased salivation has been reported [99]. Cardiac conduction abnormalities, including bradycardia and sinoatrial block, bundle branch block with runs of atrial fibrillation, extrasystoles, and bradycardia, have occurred in patients with CPH [43,61,100].…”
Section: Laboratory Studiesmentioning
confidence: 99%